Epigenetic Regulation of Phenotypic Sexual Plasticity Inducing Skewed Sex Ratio in Zebrafish - Hosseini, Shahrbanou; Trakooljul, Nares; Hirschfeld, Marc; Wimmers, Klaus; Simianer, Henner; Tetens, Jens; Sharifi, Ahmad Reza; Brenig, Bertram (Frontiers in Cell and Developmental Biology, 2022)
The plasticity of sexual phenotype in response to environmental conditions results in biased sex ratios, and their variation has an effect on population dynamics. Epigenetic modifications can modulate sex ratio variation in species, where sex is determined by genetic and environmental factors. However, the role of epigenetic mechanisms underlying skewed sex ratios is far from being clear and is still an object of debate in evolutionary developmental biology. In this study, we used zebrafish as a model animal to investigate the effect of DNA methylation on sex ratio variation in sex-biased families in response to environmental temperature. Two sex-biased families with a significant difference in sex ratio were selected for genome-wide DNA methylation analysis using reduced representation bisulfite sequencing (RRBS). The results showed significant genome-wide methylation differences between male-biased and female-biased families, with a greater number of methylated CpG sites in testes than ovaries. Likewise, pronounced differences between testes and ovaries were identified within both families, where the male-biased family exhibited a higher number of methylated sites than the female-biased family. The effect of temperature showed more methylated positions in the high incubation temperature than the control temperature. We found differential methylation of many reproduction-related genes (e.g. sox9a, nr5a2, lhx8a, gata4) and genes involved in epigenetic mechanisms (e.g. dnmt3bb.1, dimt1l, hdac11, h1m) in both families. We conclude that epigenetic modifications can influence the sex ratio variation in zebrafish families and may generate skewed sex ratios, which could have a negative consequence for population fitness in species with genotype-environment interaction sex-determining system under rapid environmental changes.